O menino sebosinho: a estratégica representação de infância na página Suricate Seboso - Sales, João Victor Melo (2016)
Since 2012, the Suricate Seboso’s fanpage, from Ceará, a state located in Northeast Brazil, has gotten success in Facebook because it publishes comics and memes that represent elements from the regional quotidian by a humoristic and regionalist style. Most of the posts brings up subjects related to childhood in its contents, by the strategic construction of a representation about this category, mainly with the feature of the character Sebosinho, which is a child. The object of this research is to identify the main sense effects within the construction strategies of the childhood representation in the content of the fanpage. By an nethnographic approach (KOZINETS, 1998; GEERTZ, 2014; FRAGOSO; RECUERO; AMARAL, 2011), that considers the cultural circulation model by Richard Johnson (2010), the methodology includes the specific analysis of 50 posts, of comments published by the fans and of interviews gave by the producers. The selected posts’ analysis identified the main representative elements of the childhood culture’s grammar (SARMENTO, 2004) which were used strategically in the edition of the contents, producing some sense effects on the audience. The discussions work with the concepts of sense effect (CHARAUDEAU, 2010), strategy (CERTEAU, 1996), representation (MOSCOVICI, 2004), childhood (QVORTRUP, 2010), childhood cultures (SARMENTO, 2004; CORSARO, 2011), ludic culture (BROUGÈRE, 1997), symbolic forms (THOMPSON, 1995), ethos (MAINGUENEAU, 1997), besides the considerations of Lipovetsky (2005) and Minois (2003) about humor, the ideas of Haesbaert (1999), Hall (2005) and Canclini (2008) about identification processes, and the discussions of Albuquerque Jr. (2003; 2006) and Carvalho (1994; 2004) about the regionalism from Northeast Brazil. The research highlight principally three main effects, which are factors that help to explain the audience success of the page: the production of identification processes, the evocation of nostalgia feeling and the publicization of private elements. They aren’t produced only for the fans, but also for the own content producers, who are amateurs that got visibility and profit with their internet activities, mainly because they create a childhood representation that reinforce the elements referred to society’s segments defined by the section of region, social class, generation and gender.